‎If $f\left(z \right)=\sum_{n=2}^{\infty}a_{n}z^n$ and $\sum_{n=2}^{\infty}|a_n|$ converges then‎, $$\sum_{n=1}^{\infty}f\left(\frac{1}{n}\right)=\sum_{n=2}^{\infty}a_n\zeta\left(n\right)‎.$$ ‎Since if we set $C:=\sum_{m=2}^{\infty}|a_m|<\infty$‎, ‎then‎ $$\sum_{n=1}^{\infty}\sum_{m=2}^{\infty}|a_m\frac{1}{n^m}|\leq\sum_{n=1}^{\infty}\sum_{m=2}^{\infty}|a_m|\frac{1}{n^2}\leq C\sum_{n=1}^{\infty}\frac{1}{n^2}<\infty‎$$ and ‎by Cauchy's double series theorem‎, ‎we can switch the order of summation‎: $$\sum_{n=1}^{\infty}f\left(\frac{1}{n}\right)=\sum_{n=1}^{\infty}\sum_{m=2}^{\infty}a_m\frac{1}{n^m}=\sum_{m=2}^{\infty}a_m\sum_{n=1}^{\infty}\frac{1}{n^m}=\sum_{n=2}^{\infty}a_n\zeta\left(n\right)‎.$$ This shows that $‎\sum_{n=2}^{\infty}\frac{\zeta(n)}{k^n}=\sum_{n=1}^{\infty}\frac{1}{kn(kn-1)}$.

My Questions:

1) It's obvious that $\sum_{n=1}^{\infty}\frac{1}{2n(2n-1)}=\log(2)$, but how can I evaluate $\sum_{n=1}^{\infty}\frac{1}{3n(3n-1)}$?

2) Is there another method to evaluate $\sum_{n=2}^{\infty}\frac{\zeta(n)}{k^n}$?

  • 2
    $\begingroup$ Generally speaking, $$\sum_{n=1}^\infty\frac1{(n+a)(n+b)}=\frac{H_a-H_b}{a-b}$$ where $$H_n=\int_0^1\frac{1-x^n}{1-x}dx$$ More information available here. In your case, $a=0$ and $b=-\frac1k$, where k is $2$, $3$, etc. $\endgroup$ – Lucian Nov 13 '13 at 12:13

Extended Harmonic Numbers

Normally, we think of Harmonic Numbers as $$ H_n=\sum_{k=1}^n\frac1k\tag{1} $$ However, an alternate definition is often useful: $$ H_n=\sum_{k=1}^\infty\left(\frac1k-\frac1{k+n}\right)\tag{2} $$ For integer $n\ge1$, it is not too difficult to see that the two definitions agree. However, $(2)$ is easily extendible to all $n\in\mathbb{R}$ (actually, to all $n\in\mathbb{C}$). We can say some things about $H_n$ for some $n\in\mathbb{Q}\setminus\mathbb{Z}$.

Note that for $m,n\in\mathbb{Z}$, $$ \begin{align} H_{mn}-H_n &=\sum_{k=1}^\infty\left(\frac1k-\frac1{k+mn}\right)-H_n\\ &=\sum_{k=1}^\infty\sum_{j=0}^{m-1}\left(\frac1{km-j}-\frac1{km-j+mn}\right)-H_n\\ &=\frac1m\sum_{j=0}^{m-1}\sum_{k=1}^\infty\left(\left(\frac1k-\frac1{k-j/m+n}\right)-\left(\frac1k-\frac1{k-j/m}\right)\right)-H_n\\ &=\frac1m\sum_{j=0}^{m-1}\left(\left(H_{n-j/m}-H_n\right)-H_{-j/m}\right)\tag{3} \end{align} $$ Since $H_0=0$ and $H_n=\log(n)+\gamma+O\left(\frac1n\right)$, where $\gamma$ is the Euler-Mascheroni Constant, if we let $n\to\infty$ in $(3)$, we get $$ \sum_{j=1}^{m-1}H_{-j/m}=-m\log(m)\tag{4} $$ Using identity $(7)$ from this answer, $$ \begin{align} \pi\cot(\pi z) &=\sum_{k\in\mathbb{Z}}\frac1{k+z}\\ &=\sum_{k=1}^\infty\left(\frac1{k-1+z}-\frac1{k-z}\right)\\ &=\sum_{k=1}^\infty\left(\frac1k-\frac1{k-z}\right)-\sum_{k=1}^\infty\left(\frac1k-\frac1{k+z-1}\right)\\ &=H_{-z}-H_{z-1}\tag{5} \end{align} $$ which implies $$ H_{-j/m}-H_{-(m-j)/m}=\pi\cot\left(\frac{\pi j}{m}\right)\tag{6} $$

Using $(4)$ and $(6)$ for $m=3$ yields $$ H_{-1/3}+H_{-2/3}=-3\log(3)\tag{7} $$ and $$ H_{-1/3}-H_{-2/3}=\pi\cot\left(\frac\pi3\right)\tag{8} $$ Averaging $(7)$ and $(8)$ yields $$ H_{-1/3}=-\frac32\log(3)+\frac\pi{2\sqrt3}\tag{9} $$ Finally, $$ \begin{align} \sum_{n=1}^\infty\frac1{3n(3n-1)} &=-\frac13\sum_{n=1}^\infty\left(\frac1n-\frac1{n-1/3}\right)\\ &=-\frac13H_{-1/3}\\[6pt] &=\frac12\log(3)-\frac\pi{6\sqrt3}\tag{10} \end{align} $$

Values for Future Reference

Using $(4)$ and $(6)$, we can also compute $$ \begin{align} H_{-1/4}&=\pi/2-3\log(2)\\ H_{-1/2}&=-2\log(2)\\ H_{-3/4}&=-\pi/2-3\log(2) \end{align}\tag{11} $$

  • 6
    $\begingroup$ Creative and very nice! And easy $\endgroup$ – dust05 Sep 26 '13 at 17:14
  • 4
    $\begingroup$ This deserves to be published. An MAA magazine seems appropriate. $\endgroup$ – marty cohen May 3 '15 at 16:34
  • 1
    $\begingroup$ $H_{p/q}$ for $0\lt p/q\lt1$ can be computed using $(7)$ from this answer. $\endgroup$ – robjohn May 2 '17 at 16:12
  • $\begingroup$ I don't recall how I found this answer, but after some searching, I believe this article / lecture notes by B Candelpergher shows that your $H_z$ is (or is related to) one of Ramanujan's summation methods. Chapter 1 definition 3 on page 22, and also the remark on page 24 hal.univ-cotedazur.fr/hal-01150208v2/document $\endgroup$ – Calvin Khor Sep 22 at 6:10

Answer to Second Question

We remark that

$$\Gamma(z)\zeta(z)=\int_0^\infty \frac{u^{z-1}}{e^u-1}du\tag{1}$$ $$\sum_{n=2}^\infty \frac{t^n}{(n-1)!}=(e^t-1)t \tag{2}$$ $$\psi_0(s+1)=-\gamma+\int_0^1 \frac{1-x^s}{1-x}dx \tag{3}$$ where $\psi_0(s)$ is Digamma Function and $\gamma$ is the Euler's Constant.


$$\begin{align*} \sum_{n=2}^\infty \frac{\zeta(n)}{k^n} &= \sum_{n=2}^\infty \frac{1}{k^n \Gamma(n)}\int_0^\infty \frac{u^{n-1}}{e^u-1}du\\ &=\int_0^\infty\frac{1}{u(e^u-1)}\left( \sum_{n=2}^\infty \frac{1}{(n-1)!}\left(\frac{u}{k}\right)^n\right)du \\ &= \frac{1}{k}\int_0^\infty \frac{e^{\frac{u}{k}}-1}{e^u-1}du \tag{4} \end{align*}$$

Substituting $t=e^{-u}$, we get

$$ \begin{align*} \sum_{n=2}^\infty \frac{\zeta(n)}{k^n}&=-\frac{1}{k}\int_0^1 \frac{1-t^{-1/k}}{1-t}dt \\ &= \frac{-1}{k}\left\{ \gamma+\psi_0 \left(1-\frac{1}{k} \right)\right\} \tag{5} \end{align*} $$

If $k(\geq 2)$ is an integer, equation $(5)$ can be further simplified using Gauss' Digamma Theorem.

$$\sum_{n=2}^\infty \frac{\zeta(n)}{k^n}=-\frac{\pi}{2k}\cot \left( \frac{\pi}{k}\right)+\frac{\log k}{k}-\frac{1}{k}\sum_{m=1}^{k-1}\cos \left(\frac{2\pi m}{k} \right) \log \left( 2\sin \frac{\pi m}{2}\right)$$


Answering you first question.
Don't know whether it's simpler but still (since you'll have to deal with hypergeometric functions). $$ \sum_{n=1}^{\infty}\frac{1}{3n(3n-1)}=\frac{1}{3}\sum_{n=1}^{\infty}\frac{1}{3n-1}\int_0^1x^{n-1} \mathrm dx=\frac{1}{3}\int_0^1\sum_{n=1}^{\infty}\frac{x^{n-1}}{3n-1}\mathrm dx$$ $$\sum_{n=1}^{\infty}\frac{x^{n-1}}{3n-1}=\frac{1}{2} \, _2F_1\left(\frac{2}{3},1;\frac{5}{3};x\right)$$ And $$\frac{1}{6} \int_0^1 \, _2F_1\left(\frac{2}{3},1;\frac{5}{3};x\right) \, \mathrm dx=\frac{1}{6} \left(3\log(3) -\frac{\pi }{\sqrt{3}}\right)$$ So $$\sum_{n=1}^{\infty}\frac{1}{3n(3n-1)}=\frac{1}{6} \left(3\log(3) -\frac{\pi }{\sqrt{3}}\right)$$


This is an aswer for every $k$, using your method. For $k=2$ and $3$ it fits with other answers, so it's probably correct :) It is completely elementary, in the sense that it uses just the Taylor expansion of $\log(1-x)$ and the fact that the sum $\sum_{\alpha^k=1}\alpha^n$ ($\alpha$ runs over the $k$-th roots of $1$) is $k$ if $k$ divides $n$ and $0$ otherwise.

There are some $\log$'s of complex numbers. Those numbers have always non-negative real part, for the Arg we take the angle between $-\pi/2$ and $\pi/2$, so that it fits with the power series for $\log(1-x)$.

$$\sum_n x^{kn}/kn=-\log(1-x^k)/k=-\frac{1}{k}\sum_{\alpha^k=1}\log(1-\alpha x)$$ $$\sum_{\alpha^k=1}\sum_{m=1}^\infty\alpha(\alpha x)^m/m=k\sum_{n=1}^{\infty}x^{kn-1}/(kn-1)$$ but also $$\sum_{\alpha^k=1}\sum_{m=1}^\infty\alpha(\alpha x)^m/m=-\sum_{\alpha^k=1}\alpha\log(1-\alpha x).$$ We thus have $$\sum_n x^{kn}/(kn(kn-1))=\sum_n x^{kn}(\frac{1}{kn-1}-\frac{1}{kn})=$$ $$=\frac{1}{k}\sum_{\alpha^k=1}(1-x\alpha)\log(1-\alpha x).$$ We have to take the limit $x\to 1$. The $\alpha=1$ term disappears, so we get $$\sum_n\frac{1}{kn(kn-1)}=\frac{1}{k}\sum_{\alpha^k=1,\alpha\neq1}(1-\alpha)\log(1-\alpha)=$$ ($\alpha=\exp(2\pi i m/k)$) $$=\frac{1}{k}\sum_{m=1}^{k-1}((1-\cos\frac{2\pi m}{k})-i\sin\frac{2\pi m}{k})(\log(2\sin\frac{\pi m}{k})+\pi i(m/k-1/2))=$$ $$=\frac{1}{k}\sum_{m=1}^{k-1}(1-\cos\frac{2\pi m}{k})\log(2\sin\frac{\pi m}{k})+\pi(m/k-1/2)\sin\frac{2\pi m}{k}.$$

  • $\begingroup$ nicely done (+1) $\endgroup$ – robjohn Sep 26 '13 at 22:15

In the intro above the question is asked how one might go about computing $$\sum_{n=1}^\infty \frac{1}{3n(3n-1)}.$$

I can contribute an asymptotic expansion and an infinite series to this discussion, shown and proved below. In addition to posting this answer I am also asking two questions I. Can you verify this expansion using a different proof technique? II. Might there even be a reference to the below formula somewhere?

This is the proof, which is procedural, with the result at the end. Suppose we seek to evaluate $$T(q) = \sum_{n\ge 1} \frac{1}{qn(qn-1)} = \sum_{n=1}^p \frac{1}{qn(qn-1)} + \sum_{n\ge 1} \frac{1}{(qn+pq)(qn+pq-1)} \\= \sum_{n=1}^p \frac{1}{qn(qn-1)} + \frac{1}{q^2}\sum_{n\ge 1} \frac{1}{(n+p)(n+(pq-1)/q)}$$ with $p, q\ge 2$ two integers.

The sum term, call it $S(x)$, is harmonic and may be evaluated by inverting its Mellin transform. Recall the Mellin transform identity for harmonic sums with base function $g(x)$, which is $$\mathfrak{M}\left(\sum_{k\ge 1}\lambda_k g(\mu_k x); s\right) = \left(\sum_{k\ge 1} \frac{\lambda_k}{\mu_k^s}\right) g^*(s)$$ where $g^*(s)$ is the Mellin transform of $g(x).$

In the present case we have $$\lambda_k = 1, \quad \mu_k = k \quad \text{and} \quad g(x) = \frac{1}{(x+p)(x+(pq-1)/q)}.$$ The Mellin transform of $g(x)$ is $$\int_0^\infty \frac{1}{(x+p)(x+(pq-1)/q)} x^{s-1} dx.$$

We chose $p\ge 2$ so that the base function does not have a pole at $x=-1$, which would cause the expansion about infinity that we eventually obtain not to converge. (As we evaluate the harmonic sum at $x=1$ this would be situated right on the boundary between the two disks about zero and about infinity, causing an evaluation at $x=1$ to fail.)

We evaluate the Mellin transform next. Use a circular contour to get $$ g^*(s) (1 - e^{2\pi i (s-1)}) \\= 2\pi i \left( \operatorname{Res}\left(\frac{x^{s-1}}{(x+p)(x+\frac{pq-1}{q})}; s=-p\right) + \operatorname{Res}\left(\frac{x^{s-1}}{(x+p)(x+\frac{pq-1}{q})}; s=-\frac{pq-1}{q}\right) \right) \\= 2\pi i \left(-q(-p)^{s-1} + q(-(pq-1)/q)^{s-1}\right) = 2\pi i e^{\pi i (s-1)} q \left(((pq-1)/q)^{s-1}-p^{s-1}\right).$$ This implies that $$g^*(s) = 2\pi i q \frac{-e^{\pi i s}}{1 - e^{2\pi i s}} \left(\left(\frac{pq-1}{q}\right)^{s-1} - p^{s-1}\right)\\= -2\pi i q \frac{1}{e^{-\pi i s} - e^{\pi i s}} \left(\left(\frac{pq-1}{q}\right)^{s-1} - p^{s-1}\right) \\= q\pi\frac{2i}{e^{\pi i s} - e^{-\pi i s}} \left(\left(\frac{pq-1}{q}\right)^{s-1} - p^{s-1}\right) = q\frac{\pi}{\sin(\pi s)} \left(\left(\frac{pq-1}{q}\right)^{s-1} - p^{s-1}\right).$$

It follows that the Mellin transform of the sum term for $S(x)$ is given by $$ Q(s) = q \frac{\pi}{\sin(\pi s)} \left(\left(\frac{pq-1}{q}\right)^{s-1} - p^{s-1}\right) \zeta(s) \quad\text{because}\quad \sum_{k\ge 1} \frac{\lambda_k}{\mu_k^s} = \zeta(s).$$

Finally we invert the Mellin transform with the inversion integral $$\frac{1}{2\pi i}\int_{3/2-i\infty}^{3/2+i\infty} Q(s)/x^s ds$$ to obtain an expansion about infinity of $S(x)$ starting with the pole at $s=2$ and getting $$ S(x) \sim - q \sum_{m\ge 2} (-1)^m \left(\left(\frac{pq-1}{q}\right)^{m-1} - p^{m-1}\right) \frac{\zeta(m)}{x^m}.$$

Setting $x=1$ and substituting into the original equation we finally have $$ T(q) = \sum_{n=1}^p \frac{1}{qn(qn-1)} - \frac{1}{q} \sum_{m\ge 2} (-1)^m \left(\left(\frac{pq-1}{q}\right)^{m-1} - p^{m-1}\right) \zeta(m).$$

Addendum Wed Apr 2 20:14:50 CEST 2014. The following MSE link shows how to work with divergent Mellin transforms where there is a pole on the positive real axis (even ones).

  • $\begingroup$ Dear Teacher, I'm so sorry for this comment..I asked a question in MSE and I waited for days..(with the 100+ bountry)..But, unfortunately, I did not get a satisfactory answer...I would like to ask..If You have a few minutes, can you look my problem, Please?.. (I'm sorry for wrong words, English is my second language).. Thank you very much.. math.stackexchange.com/q/2736937/460967 $\endgroup$ – Elvin Jul 7 '18 at 6:52

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ \begin{align} &\color{#c00000}{\sum_{n = 2}^{\infty}{\zeta\pars{n} \over k^{n}}} =\sum_{n = 2}^{\infty}{1 \over k^{n}} \sum_{\ell = 0}^{\infty}{1 \over \pars{\ell + 1}^{n}} =\sum_{\ell = 0}^{\infty}\sum_{n = 2}^{\infty}{1 \over \bracks{k\pars{\ell + 1}}^{n}} =\sum_{\ell = 0}^{\infty} {\bracks{k\pars{\ell + 1}}^{-2} \over 1 - \bracks{k\pars{\ell + 1}}^{-1}} \\[3mm]&={1 \over k^{2}}\sum_{\ell = 0}^{\infty} {1 \over \pars{\ell + 1}\pars{\ell + 1 - 1/k}} ={1 \over k^{2}}\,{\Psi\pars{1} - \Psi\pars{1 - 1/k} \over 1 - \pars{1 - 1/k}} \\[3mm]&=\color{#c00000}{% {1 \over k}\bracks{\Psi\pars{1} - \Psi\pars{1 - {1 \over k}}}} \end{align} where $\ds{\Psi\pars{z}}$ is the Digamma Function.

$$ \color{#00f}{\large\sum_{n = 2}^{\infty}{\zeta\pars{n} \over k^{n}} =-\,{1 \over k}\,\bracks{\gamma + \Psi\pars{1 - {1 \over k}}}}\,,\qquad\verts{k} > 1 $$ since $\ds{\Psi\pars{1} = -\gamma.\quad}$ $\gamma$ is the Euler-Mascheroni Constant.

$\large\tt\mbox{Just one of your questions !!!}$: \begin{align} \sum_{n = 1}^{\infty}{1 \over 3n\pars{3n - 1}}& ={1 \over 9}\sum_{n = 1}^{\infty}{1 \over n\pars{n - 1/3}} ={1 \over 9}\sum_{n = 0}^{\infty}{1 \over \pars{n + 1}\pars{n + 2/3}} ={1 \over 9}\,{\Psi\pars{1} - \Psi\pars{2/3} \over 1 - 2/3} \\[3mm]&={1 \over 3}\,\bracks{\Psi\pars{1} - \Psi\pars{{2 \over 3}}} \quad\quad\quad\quad\quad\quad\quad\quad\quad\quad\quad\quad\quad\quad\quad\quad\quad\pars{1} \end{align} Also,

$$ \Psi\pars{{2 \over 3}} = -\gamma + {\root{3} \over 6}\,\pi - {3 \over 2}\,\ln\pars{3} $$ By replacing in $\pars{1}$, we'll find:

$$ \color{#00f}{\large\sum_{n = 1}^{\infty}{1 \over 3n\pars{3n - 1}} ={1 \over 18}\bracks{9\ln\pars{3} - \root{3}\pi}} \approx 0.2470 $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.